PROFIL LIPID DAN TATALAKSANA PADA PENDERITA XANTHELASMA PALPEBRARUM - Reynhard Theodorus Xaverius Saragih; Sutarto; Winda Trijayanthi Utama (CV. Jasa Sukses Abadi, 2023)
Xanthelasma palpebrarum is the occurrence of yellowish flat lesions around the eyelids. Xanthelasma is generally found in adults over the age of fifty. It is not known exactly how xanthelasma can occur, but xanthelasma is thought to be related to atherosclerosis. In this study, lipid profile analysis and management of xanthelasma patients were carried out. Literature collection was carried out with the inclusion criteria in the form of literature published maximum in 2012. Meanwhile, the exclusion criteria were in the form of literature published in 2011 and below. The results of the study showed increased levels of serum cholesterol, triglycerides, VLDL, and HDL in xanthelasma patients. This study also found an increase in Epicardial Adipose Tissue (EAT) in xanthelasma patients, which these findings indicate that there is a relationship between xanthelasma and atherosclerosis.